POVERTY AND INEQUALITY ANALYSIS OF POPULATION EXPENDITURE IN WEST NUSA TENGGARA - IRWAN, MUHAMMAD; HARSONO, IWAN; MARYAM, ST.; AWWALUNNISA, NUR (GANEC SWARA, 2023)
This study aims to analyze and describe the development of poverty and inequality of population expenditure in West Nusa Tenggara. The research method used is descriptive research using secondary data from 2014-2021. The analysis technique used in this study was analyzing data using tables related to the aspects studied: population expenditure data analysis to determine inequality occurrence using the Gini efficiency and the World Bank criteria.The results show that the development of the number of poor people has always decreased, with the number of poor people in rural areas being smaller than in urban areas. The distribution of the poverty line in both urban and rural areas averaged more than 70% for food needs, the remaining less than 30% for non-food needs. On average, the percentage of poor people during 2014-2021 for urban and rural areas is 15,15%. The average poverty depth index (P1) was 2.700 for urban and rural areas, and the average poverty severity index (P2) during the year was 0,670%.The average inequality of population expenditure based on the Gini coefficient is 0.379 for urban and rural areas, which is “moderate”. Based on World Bank criteria, inequality of population expenditure in rural areas is classified as “mild or low inequality,” while in urban areas, it is classified as “moderate inequality.” Expenditure inquality for rural and urban areas is classified as “mild or low inequality.”